A critical review of systematic reviews and meta-analyses of curcumin for knee osteoarthritis - Chen, Jixin; Zhou, Qinxin; Yu, Weijie; Cao, Dongdong; Li, Yingzhou; Chen, Jianliang; Ye, Feng (Frontiers in Pharmacology, 2026)
ObjectiveThis study aims to assess the efficacy of curcumins in treating knee osteoarthritis (KOA).MethodsWe performed a comprehensive review of literature from inception to 11 January 2025, identifying all systematic reviews (SRs) and meta-analyses (MAs) on curcumin treatment for KOA. Two independent reviewers conducted literature screening and data extraction. Evaluation of methodological and reporting quality, risk of bias, evidence quality, and evidence overlap was carried out using AMSTAR 2, PRISMA 2020, ROBIS, GRADE, and GROOVE frameworks.ResultsSeven SRs met inclusion criteria. Curcumins demonstrated potential efficacy and safety advantages over control treatments in KOA management. However, these reviews were of extremely low methodological quality, with poor reporting and significant information gaps. High risk of bias was noted in four SRs. Among 48 outcomes assessed, evidence quality was mostly low, with 5 medium-quality, 6 low-quality, and 37 extremely low-quality evidences. Significant literature overlap was evident.ConclusionThe current SRs on curcumins for KOA are of low quality. Future research should adhere to rigorous quality assessment standards, increase sample sizes to minimize overlap, and thoroughly evaluate evidence quality to enhance the reliability and rigor of evidence supporting clinical practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42025641801, identifier CRD42025641801.